Geologi Dan Pengaruh Struktur Geologi Terhadap Kualitas Batubara pada Satuan Batupasir Kampungbaru Daerah Mutiara dan Sekitarnya Kecamatan Samboja Kabupaten Kutai Kartanegara Provinsi Kalimantan Timur - Ridho Muhari; Ediyanto Ediyanto; Harman Dwi R (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2016)
Study area is located in Mutiara and surrounding area, Samboja District, Kutai Kartanegara Regency,East Kalimantan Province. At coordinates 0° 56’ 43’’ - 0° 59’ 26’’ South Latitude and 117° 1’ 37’’ - 117°3’ 46’’ East Longitude or UTM N 9890500 - 9895500 and E 503000 - 507000. The objective of thisstudy is to identify geological conditions and the influence of geological structure toward to quality ofcoal in the study area. The stratigraphy of study area composed by 3 rock units and 1 unconsolidatedfrom old to young are Balikpapan sandstone unit (Middle Miocene - Late Miocene) deposited in LowerDelta Plain, Kampungbarusandstone unit (Late Miocene - Pliocene) deposited in Lower Delta Plain,and Quarter Alluvial (Holocene). From proximate analyses, coal seam Kampungbaru Sandstone Unitcontain low sulfur and low calories, and high total moisture due to presence of two normal faults fromsubsurface interpretation that formed simultaneously with peatification process on coal seamKampungbaru Sandstone unit. Those normal faults resulted water increase on peatificationenvirontment that caused aerobic bacteria can not completely ondestruction of plant components thatwill form high sulfur and low calories and high total moisture.